2019
DOI: 10.1002/cctc.201900548
|View full text |Cite
|
Sign up to set email alerts
|

Human Fatty Acid Synthase: A Computational Study of the Transfer of the Acyl Moieties from MAT to the ACP Domain

Abstract: Human Fatty Acid Synthase (hFAS) is a multidomain enzyme responsible for the biosynthesis of saturated fatty acids, which are crucial for numerous biological processes. During the biosynthetic reaction, hFAS incorporates acetyl and malonyl moieties through the action of its malonyl‐acetyl transferase (MAT) domain. These precursor molecules are transferred from CoA to the acyl‐carrier protein (ACP) domain by a two‐stage ping‐pong catalytic mechanism. The first stage, during which the acyl moieties are relocated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 60 publications
(62 reference statements)
2
30
0
Order By: Relevance
“…On the other hand, the reaction Gibbs free energies (∆G R ) were calculated through the difference between the energy of product and reactant for each step. This computational approach has already been successfully employed to study the catalytic mechanism of several enzymes [56][57][58][59][60][61][62], including proteases [63][64][65].…”
Section: Qm/mm Modelmentioning
confidence: 99%
“…On the other hand, the reaction Gibbs free energies (∆G R ) were calculated through the difference between the energy of product and reactant for each step. This computational approach has already been successfully employed to study the catalytic mechanism of several enzymes [56][57][58][59][60][61][62], including proteases [63][64][65].…”
Section: Qm/mm Modelmentioning
confidence: 99%
“…She is the author of just over 400 scientific publications, 5 books and 12 book chapters. Most of her scientific work has been devoted to her research in computational biochemistry, namely computational enzymology and drug discovery …”
mentioning
confidence: 99%
“…The computational analysis identified the first step as rate-limiting for the full MAT-mediated reaction. [135] Type I and II ATs from FASs and PKSs show similar folds. [3,41,69,99,136,137] They comprise a core domain with an ↵/ -hydrolase-like structure and a smaller subdomain with a ferrodoxin-like structure (Fig.…”
Section: The Acyl Transferasementioning
confidence: 94%
“…[41] Recently, P. Paiva and co-workers analyzed the reactions mediated by the human MAT in mechanistic detail using quantum mechanics/molecular mechanics (QM/MM) calculations. [134,135] They showed that both steps, the AT-loading ping and the ACP-loading pong step, occur in two sequential steps. The first step consists of the concerted deprotonation of Ser581 by His683 and the nuceophilic attack of the substrate thioester carbonyl carbon by the deprotonated Ser581, leading to a tetrahedral intermediate.…”
Section: The Acyl Transferasementioning
confidence: 99%
See 1 more Smart Citation